PROPOSED HIGHER ORDER CONTINUUM-BASED MODELS FOR AN ELASTIC SUBGRADE - Worku, Asrat (Zede Journal of Ethiopian Engineers and Architects, 2023)
Three new variants of continuum-based models for an elastic subgrade are proposed. The subgrade is idealized as a homogenous, isotropic elastic layer of thickness H overlying a firm stratum. All components of the stress tensor in the subgrade are taken into account. Reasonable assumptions are made regarding the depth-wise variation of the vertical shear stress components and of the horizontal-to-vertical normal stress ratios to simplify mathematical work. The assumptions are based on observation of available analytical results of stress distributions and on knowledge of lateral earth pressure theories. The resulting differential equations are similar in form and order to a high-order model developed earlier by Reissner based on a number of simplifying assumptions, but with different coefficients dependant on Poisson ratio. With the help of appropriately selected mechanical models, it has been shown that all of the new model variants consistently give larger effective vertical stiffness and larger shear interaction among the classical Winkler springs for the range of Poisson ratio of practical interest.